2022
DOI: 10.1007/s00418-022-02115-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the role of Rab11-positive recycling endosomes as intermediates in coronavirus egress from epithelial cells

Abstract: After their assembly by budding into the lumen of the intermediate compartment (IC) at the endoplasmic reticulum (ER)–Golgi interface, coronaviruses (CoVs) are released from their host cells following a pathway that remains poorly understood. The traditional view that CoV exit occurs via the constitutive secretory route has recently been questioned by studies suggesting that this process involves unconventional secretion. Here, using the avian infectious bronchitis virus (IBV) as a well-established model virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Importantly, however, this relationship is conserved on RSV and SeV vRNA-trafficking vesicles. While the data discussed here directly present strong evidence for the importance of myoferlin for vRNA trafficking of IAV, RSV and SeV specifically, they imply that this would also be the case for all Rab11a-dependent viruses, including coronaviruses, 10 parainfluenza viruses, 9 Hantaviruses, 4 ebolaviruses 6 and flaviviruses. 5…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Importantly, however, this relationship is conserved on RSV and SeV vRNA-trafficking vesicles. While the data discussed here directly present strong evidence for the importance of myoferlin for vRNA trafficking of IAV, RSV and SeV specifically, they imply that this would also be the case for all Rab11a-dependent viruses, including coronaviruses, 10 parainfluenza viruses, 9 Hantaviruses, 4 ebolaviruses 6 and flaviviruses. 5…”
Section: Discussionmentioning
confidence: 67%
“…While only three respiratory viruses that utilise Rab11a-mediated vRNP trafficking were investigated here, these data imply a conserved role for myoferlin in the replication of other Rab11-dependent viruses, including respiratory pathogens of the Coronaviridae and Paramyxoviridae families. 3,10,47…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our findings and results of previous studies indicate that βCoVs, such as PHEV, SARS-CoV-2, and MHV, employ a lysosome-based egress pathway rather than a biosynthetic secretory egress pathway ( 6 ). Meanwhile, Saraste et al have reported evidence indicating that Rab11-positive recycling endosomes may function as transport carriers during the cellular exit of avian infectious bronchitis virus, a γCoV ( 24 ). Thus, conflicting findings concerning the roles of secretory compartments in CoV egress suggest that CoVs belonging to different genera may exit cells via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Coronaviruses assembly occurs by their budding in the lumen of the intermediate compartment, a subcellular vesiculo-tubulo structure located at the endoplasmic reticulum–Golgi apparatus interface (Saraste et al 1987 ). The poorly understood release pathway of coronaviruses from their host cells was investigated by Saraste et al ( 2022 ) by employing confocal immunofluorescence microscopy. Virus infection resulted in the accumulation of recycling endosomes defined by the GTPase Rab11 next to the centrosome, which was intimately linked to virus-induced Golgi fragmentation and virus release.…”
mentioning
confidence: 99%